La faute à DEWEY. À propos de quelques contresens sur sa philosophie de l'éducation - Michel Fabre (Nantes Université, 2017)
During the educational crisis of the 1960s in the United States, intellectuals like Hannah Arendt blame educational thought of John Dewey. He would promote chidren's self gouverning, emphasize the pedagogical approach at the expense of content, substitute the know how to knowledge. The charges are indefinitely repeats by anti-pedagogical criticism raging in France since the 1980s. This article attempts here to make the difference between the real pedagogical thinking of Dewey and the drifts from some of his followers, drifts Dewey convicted himself. But these excesses have contributed to the misinterpretation of the pragmatist philosophy of education. It will also point out the critical resources of the thought of Dewey in respect of a number of past and present educational presuppositions, so called common sense.